Human Urine as a Noninvasive Source of Kidney Cells - Fanny Oliveira Arcolino; Agnès Tort Piella; Elli Papadimitriou; Benedetta Bussolati; Daniel J. Antonie; Patricia Murray; Lamberthus van den Heuvel; Elena Levtchenko (Hindawi Limited, 2015)
Urine represents an unlimited source of patient-specific kidney cells that can be harvested noninvasively. Urine derived podocytes and proximal tubule cells have been used to study disease mechanisms and to screen for novel drug therapies in a variety of human kidney disorders. The urinary kidney stem/progenitor cells and extracellular vesicles, instead, might be promising for therapeutic treatments of kidney injury. The greatest advantages of urine as a source of viable cells are the easy collection and less complicated ethical issues. However, extensive characterization and in vivo studies still have to be performed before the clinical use of urine-derived kidney progenitors.